Models Of Strengthening Islamic Religious Education Based On Boarding Schools At State Madrasah Aliyah 1 Banyuwangi, Indonesia - Moh Mundzir, Moh Mundzir; Mukni’ah; Mundir Rosyadi (International Journal of Educational Research & Social Sciences, 2023)
The model of strengthening Islamic Religious Education Based on Islamic Boarding Schools is one form of model in an effort to produce quality and character madrasa graduates. Therefore the existence of a pesantren-based PAI strengthening model can increase the competitiveness of madrasah, build their popularity, and strengthen the bargaining position of madrasah as superior madrasah Based on this background, the focus of this research is how the pesantren-based madrasah model strengthens Islamic Religious Education at State Madrasah Aliyah 1 Banyuwangi. The purpose of this study was to analyze the pesantren-based madrasah model to strengthen PAI at State Madrasah Aliyah 1 Banyuwangi. The approach used in this research is qualitative research, with the type of case study research. The research subjects used purposive sampling. Data collection techniques through observation, interviews and documentation. Data analysis techniques use the Miles, Huberman and Saldana models with data condensation, data display, data collection verification. The data validity technique is carried out through source triangulation techniques and technical triangulation. The results of this study are that the Islamic Boarding School-based Madrasah concept necessitates synchronization between PAI subjects in madrasah and Islamic Religious Education subjects in Islamic boarding schools. Madrasah Aliyah and Islamic Boarding School are in one management system and in one educational complex.